2015
DOI: 10.5152/ucd.2015.2843
|View full text |Cite
|
Sign up to set email alerts
|

Should appendectomy be performed laparoscopically? Clinical prospective randomized trial

Abstract: Objective: Laparoscopic appendectomy (LA) has been described in 1983, and its superiority over open appendectomy (OA) is still being debated. Currently, there is no agreement on the advantages of LA. Postoperative pain is reported to be lower along with a faster return to normal activities in LA. However, some studies do not support these findings. In our study, we aimed to compare the outcomes and cost effectiveness of LA and OA. Material and Methods:Patients were prospectively randomized into LA (31 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
(25 reference statements)
2
17
0
Order By: Relevance
“…Another study conducted by Rohr et al (15) reported increased number of wound site infections in the LA group. Mantoglu et al (16) determined that the wound site infection was localized at the trocar site where the appendix is extracted from the abdomen, and contamination of the skin by the appendectomy piece that is too large to fit inside the trocar, and suggested that risk of wound site infection could be minimized by placing the appendix inside a protective bag while extracting it from the abdomen in such cases. In our study, wound infection was defined as stage 1 according to Clavien-Dindo classification which was found in 21 patients in LA group, and 102 patients in OA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by Rohr et al (15) reported increased number of wound site infections in the LA group. Mantoglu et al (16) determined that the wound site infection was localized at the trocar site where the appendix is extracted from the abdomen, and contamination of the skin by the appendectomy piece that is too large to fit inside the trocar, and suggested that risk of wound site infection could be minimized by placing the appendix inside a protective bag while extracting it from the abdomen in such cases. In our study, wound infection was defined as stage 1 according to Clavien-Dindo classification which was found in 21 patients in LA group, and 102 patients in OA group.…”
Section: Discussionmentioning
confidence: 99%
“…The higher cost associated with LA was attempted to be reduced by preferring reusable endoscopic tools. Mantoglu et al (16) succeeded in partially reducing the cost by using a special set comprised of reusable trocar and hand tools and knots they had prepared using 2.0 polyglycolic acid suture instead of utilizing preformed knots. In our study, the main cause of the difference in costs between the groups was the vessel closure and sealing device.…”
Section: Discussionmentioning
confidence: 99%
“…Categorical variables – sex, ASA, MSB level, drain usage, pathologic diagnosis, intraoperative and postoperative adverse events, and patient satisfaction – were evaluated as patient numbers and percentages. Based on a previous study [ 6 ], VAS on the 1 st postoperative day was 1.61 ±0.95 after the laparoscopic appendectomy under general anesthesia. Power analysis with α = 0.05 and β = 0.2 for detecting 50% reduction in VAS after laparoscopic appendectomy under spinal/epidural anesthesia revealed that each group required a minimum of 22 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The camera is introduced from one of these and grasper is inserted from the other one, then the appendix is caught and both trocars are pulled out together (Figure 2 subject of many discussions. According to the results obtained from the studies conducted, the place of laparoscopic endoscopy has not been clarified yet (6)(7)(8).…”
Section: Techniquementioning
confidence: 99%